(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This essay presents a reflection on the work Transfiguration (1998) by Olivier de Sagazan (1959–), a piece involving the manipulation of masks as a possibility for the creation of multiple beings, using clay and other materials. The performance is understood not as a place of representation, but as a real action of a body in experience, traversed by affections, desires, and meanings. In his work, we are invited to reflect on the very idea of what a human body would be, analyzing the relationship between the materiality of the object, the human body, and the place. By analyzing the masking process and the composition of the scenographic elements, the text examines how they contribute to the appreciation of the performance.